2021
DOI: 10.3389/fonc.2021.665246
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Circular RNA in Gastrointestinal Tumors

Abstract: circular RNA (circRNA) is a closed ring structure formed by cyclic covalent bonds connecting the 5’-end and 3’-end of pre-mRNA. circRNA is widely distributed in eukaryotic cells. Recent studies have shown that circRNA is involved in the pathogenesis and development of multiple types of diseases, including tumors. circRNA is specifically expressed in tissues. And the stability of circRNA is higher than that of linear RNA, which can play biological roles through sponge adsorption of miRNA, interaction with RNA b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 135 publications
(131 reference statements)
0
3
0
Order By: Relevance
“…At present, dye leakage method, microbial infiltration method, fluid filtration method, electrochemical method, glucose leakage method, scanning electron microscope [28] are different detection methods used to evaluate dental microleakage. Due to the different theories of these methods, their results cannot be compared with each other.…”
Section: Detection and Evaluation Of Microleakagementioning
confidence: 99%
“…At present, dye leakage method, microbial infiltration method, fluid filtration method, electrochemical method, glucose leakage method, scanning electron microscope [28] are different detection methods used to evaluate dental microleakage. Due to the different theories of these methods, their results cannot be compared with each other.…”
Section: Detection and Evaluation Of Microleakagementioning
confidence: 99%
“…CircRNAs, first found in the 1890s [128], remain enigmatic owing to technological limitations and limited existing knowledge. In 2013, Hansen TB et al first proposed and confirmed that circRNAs function as miRNA sponges [129].…”
Section: Circrna In the Wnt Pathwaymentioning
confidence: 99%
“…Gastrointestinal (GI) cancers are among the most important causes of cancer-related death worldwide and mainly include colorectal cancer (CRC), gastric cancer (GC) and esophageal cancer (EC) (Wang D.-K. et al, 2021). These GI cancers pose a huge threat to human health worldwide (Fang et al, 2021). Conventional treatments, including chemotherapy, radiotherapy and surgery, have been the mainstays of cancer therapy (Buckley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%